Vocational outcomes for persons with severe physical disabilities: design and implementation of workplace supports. - Inge KJ; Strobel W; Wehman P; Todd J; Targett P (NeuroRehabilitation, 2000)
Clearly, the need for a skilled labor pool is great in today's economy. Yet, many people with significant disabilities are struggling to find jobs with the majority of them unemployed or underemployed [6]. There is a need to develop strategies that can effectively empower these individuals to become part of the nation's labor force. This article describes one model project that used person-centered career plans, supported employment, and on-the-job assistive technology assessment and training to assist 21 individuals to become competitively employed. Customers worked an average of 15.66 months earning an average of $7,271 in total wages. They were hired by both small and large businesses to do a variety of tasks to include data entry, customer service, clerical assistance, as well as food prep. While the findings are preliminary, the results indicate that individuals with severe physical disabilities can maintain employment by combining supported employment and assistive technology within the workplace.